Rancang Bangun Sistem Monitoring Digester Biogas Berbasis IoT dengan Sensor Multi-Parameter - Zainal Abidin; Nur Azizah Affandy; Eko Wahyu Santoso (Universitas Darul Ulum, 2025)
This research aims to design and implement a monitoring system for key parameters in the biogas production process, namely temperature, humidity, and pH of cow dung liquid using Internet of Things (IoT) technology. This system is designed to support the efficiency and reliability of the anaerobic fermentation process in a biogas plant digester developed in a livestock environment. A DHT11 sensor is used to measure temperature and humidity, while an analog pH sensor is used to measure the acidity level of the liquid in the digester. All data is transmitted in real time via an ESP8266 module to the ThingSpeak cloud platform, which allows for online data visualization and analysis. Test results show that the system is able to operate stably with an accuracy of ±1°C for temperature, ±3% for humidity, and ±0.2 for pH compared to conventional measuring instruments. This system is expected to assist farmers in continuously monitoring biogas conditions and become the basis for automation of fermentation process control in the future.